Metal Complexes of Mixed Ligands (Quinolone Antibiotics and α-Aminonitrile Derivatives) Their Applications: An Update with Fe (III), Co (II) and Ni (II) Ions and Study the Biological Activity - Aseel H. Abd Al-Ameer (Journal of Global Pharma Technology, 2019)
Quinolones (ciprofloxacin) have abroad- antibiotics spectrum with best oral absorbing. Consequent to the biological action located on nucleus of CH3COOH which works in the 3-location and in best state a piperazinyl base circle (or any type of N-heterocycle) at 7- positron and an oxygen carbonyl atom at 4-position). Quinolones (L1) and 2-phenyl-2-(1-Naphthylamitie) acetonitrile (L2) can bind to the ions for metal return making complexes which acting as binary ligand. The complexes and ligands which diagnosed by Micro element analysis chloride container, FTIR, UV-Vis spectra, conductivity in addition to measurement of magnetic susceptibility. Under this act founding the likely geometries shapes were proposed as octahedral complexes, several of them were classified as non-electrolyte the rest consider as weak electrolyte. The L1and L2 with [Fe(III),Co(II) and Ni(II)] respectively provided the formulae:   [ML1L2 Cl]Cl.2H2O and [FeL1L2Cl]2H2O       Were M:{ Co2+ and  Ni2+}Keywords: Quinolones (ciprofloxacin), 2-phenyl-2- (1-Naphthylamine) acetonitrile.